Comparison of Tools for Quantifying the Environmental Performance of an Urban Territory. (30th May 2017) - Dias, Ana; Lemos, Diogo; Gabarrell, Xavier; Arroja, Luis
Summary: To support effective urban policies aimed at decreasing the environmental impacts of cities, it is important to develop robust tools for accounting those impacts. Environmentally extended input‐output analysis (EEIOA) is among the most used tools for this purpose, allowing the quantification of both direct and indirect impacts. Life cycle assessment (LCA) is also a holistic and comprehensive tool that accounts for direct and indirect impacts—but its application to cities is still very recent. This study aims at applying EEIOA and LCA to the municipality of Aveiro (Portugal) in order to compare the outcomes of the two tools in terms of total impacts (climate change and fossil fuel depletion) and hotspots (sectors/products contributing most to the impacts), to identify limitations and advantages of the tools when applied to Aveiro, and to illustrate how LCA can be applied to cities. The total impacts estimated with LCA and EEIOA were similar and the hotspots were also the same: transports, food, construction, and electricity. However, the relative contribution of some sectors was very different in the two tools due to methodological differences mainly in system boundaries, type of activities or products considered in each sector, and geographical coverage of impact data. This study concludes that the analyzed tools can provide complementary results to support decision making concerning urban planning and management.